Ecological Characterization of the Colonic Microbiota of Normal and Diarrheic Dogs - Bell, Julia A.; Kopper, Jamie J.; Turnbull, Judy A.; Barbu, Nicholas I.; Murphy, Alice J.; Mansfield, Linda S. (Interdisciplinary Perspectives on Infectious Diseases, 2008)
We used terminal restriction fragment polymorphism (T-RFLP) analysis to assess (1) stability of the fecal microbiota in dogs living in environments characterized by varying degrees of exposure to factors that might alter the microbiota and (2) changes in the microbiota associated with acute episodes of diarrhea. Results showed that the healthy canine GI tract harbors potential enteric pathogens. Dogs living in an environment providing minimal exposure to factors that might alter the microbiota had similar microbiotas; the microbiotas of dogs kept in more variable environments were more variable. Substantial changes in the microbiota occurred during diarrheic episodes, including increased levels of Clostridium perfringens, Enterococcus faecalis, and Enterococcus faecium. When diet and medications of a dog having a previously stable microbiota were changed repeatedly, the microbiota also changed repeatedly. Temporal trend analysis showed directional changes in the microbiota after perturbation, a return to the starting condition, and then fluctuating changes over time.